2016
DOI: 10.4172/2327-5073.1000260
|View full text |Cite
|
Sign up to set email alerts
|

A New Sandwich ELISA Test Simultaneously Detecting E7 Proteins of HPV-16, 18 and 45 in Cervical Smears

Abstract: Persistent infections by high-risk papilloma viruses (HPV) are the main etiological factor for cervical cancer, and E7 oncoproteins were suggested as new markers for tumor progression. The objective of this study was to generate a new Enzyme-Linked Immunosorbent Assay (ELISA)-based detection system to monitor expression of the E7 proteins of the high-risk HPV (hrHPV) types HPV-16, HPV-18, and HPV-45 in cervical smears. Using a combination of rabbit monoclonal antibodies raised against E7 proteins of HPV-16 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
0
3
0
1
Order By: Relevance
“…As known, E6 and E7 transforming proteins are consistently expressed in HPV life cycle [3941]. Several studies have shown the induction of antibody responses against E6 and E7 oncoproteins in patients with cervical cancer higher than in healthy subjects [39, 42, 43]. These studies and other reports usually indicated HPV seroreactivity for cancer patients in early or late stage; but our study showed a high seroreactivity in women-exposed to high-risk HPV types (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As known, E6 and E7 transforming proteins are consistently expressed in HPV life cycle [3941]. Several studies have shown the induction of antibody responses against E6 and E7 oncoproteins in patients with cervical cancer higher than in healthy subjects [39, 42, 43]. These studies and other reports usually indicated HPV seroreactivity for cancer patients in early or late stage; but our study showed a high seroreactivity in women-exposed to high-risk HPV types (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of hrHPVE7 protein was performed via a hrHPVE7 Sandwich ELISA which was developed in a collaboration between the laboratories of Innsbruck University and Mikrogen GmbH, Neuried, Germany during the PIPAVIR project (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…The recom Well Keratin 5/8/18 ELISA has potential to serve as a test for sample validation in a range of cervical cancer screening tests. Future prospects include ELISAs developed for detection of elevated tumor suppressor protein p16, and HPV oncoprotein E7 [11,21,39,40]. A dual staining cytology technique for p16 and Ki-67 shows much promise [12].…”
Section: Discussionmentioning
confidence: 99%